ISLAM NUSANTARA: CORAK KEISLAMAN INDONESIA DAN PERANNYA DALAM MENGHADAPI KELOMPOK PURITAN - Azisi, Ali Mursyid (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2022)
Currently, Archipelagic Islam (Islam Nusantara) is a familiar term to Indonesian people. In addition to giving a dystinctive color to Islam, it also promotes diversity, by adapting Islamic values into the local culture. Islam Nusantara brings forward moderate understanding of Islam by accepting differences, promoting well-being, tolerance, mutual respect and peace. On the other side, the puritans do not regard the culture as a national identity based on textualist interpretation of the Qur’an ultimately leading to violence, coercion, infidelity, misleading and intolerance. This paper will examine what Islam Nusantara means and what kind of Islam that it promotes and how it plays a role in safeguarding the unity of the Republic of Indonesia from the puritan groups who are easily to label others as infidels for not practicing Islam as found in the Middle East.